Pengaruh Perencanaan Pajak Terhadap Manajemen Laba dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Dinar Ambarita; Ambar Tri Utami; Ibrohim Ibrohim (Publikasi Indonesia, 2023)
This study aims to test and prove empirically the effect of tax planning on earnings management with firm size as a moderating variable. This research was conducted on Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2017-2021 Period. The type of research used is quantitative. The population in this study is the annual financial report from the period 2017 to 2021, which is as many as 65 which are the samples in this study. This study uses a quantitative approach with purposive sampling in sampling. Statistical testing using Eviews 9. The results of this study indicate that Tax Planning has a partial effect on Earnings Management and Company Size can moderate the relationship between Tax Planning and Earnings Management.